+0

0
62
1

please someone i know i can do them seperate using a rule, but its hard this one

Guest Nov 15, 2017
Sort:

#1
+1

Find the derivative of the following via implicit differentiation:
d/dx(y) = d/dx((x^(1/3) + sqrt(x) + x)/x^2)

The derivative of y is y'(x):
y'(x) = d/dx((x^(1/3) + sqrt(x) + x)/x^2)

Use the product rule, d/dx(u v) = v ( du)/( dx) + u ( dv)/( dx), where u = 1/x^2 and v = x + sqrt(x) + x^(1/3):
y'(x) = (x^(1/3) + sqrt(x) + x) d/dx(1/x^2) + (d/dx(x^(1/3) + sqrt(x) + x))/(x^2)

Use the power rule, d/dx(x^n) = n x^(n - 1), where n = -2: d/dx(1/x^2) = d/dx(x^(-2)) = -2 x^(-3):
y'(x) = (d/dx(x^(1/3) + sqrt(x) + x))/x^2 + (x^(1/3) + sqrt(x) + x) (-2)/x^3

Differentiate the sum term by term:
y'(x) = -(2 (x^(1/3) + sqrt(x) + x))/x^3 + (d/dx(x^(1/3)) + d/dx(sqrt(x)) + d/dx(x))/x^2

Use the power rule, d/dx(x^n) = n x^(n - 1), where n = 1/3: d/dx(x^(1/3)) = d/dx(x^(1/3)) = x^(-2/3)/3:
y'(x) = -(2 (x^(1/3) + sqrt(x) + x))/x^3 + (d/dx(sqrt(x)) + d/dx(x) + 1/(3 x^(2/3)))/x^2

Use the power rule, d/dx(x^n) = n x^(n - 1), where n = 1/2: d/dx(sqrt(x)) = d/dx(x^(1/2)) = x^(-1/2)/2:
y'(x) = -(2 (x^(1/3) + sqrt(x) + x))/x^3 + (1/(3 x^(2/3)) + d/dx(x) + 1/(2 sqrt(x)))/x^2

The derivative of x is 1:
y'(x) = -(2 (x^(1/3) + sqrt(x) + x))/x^3 + (1/(3 x^(2/3)) + 1/(2 sqrt(x)) + 1)/x^2

Simplify the expression:
y'(x) = (1 + 1/(3 x^(2/3)) + 1/(2 sqrt(x)))/x^2 - (2 (x^(1/3) + sqrt(x) + x))/x^3 - Courtesy of "Mathmatica 11 Home Edition"

Guest Nov 15, 2017

### 11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details